THE INFLUENCE OF IRON POWDER AND DISINTEGRATED STEEL SCRAP ADDITIVES ON THE SOLIDIFICATION OF CAST IRON (Metallurgy and Foundry Engineering, 2010)
The study proves that by introducing the iron powder and disintegrated steel scrap to low-sulphur cast iron still before the inoculation carried out with a conventional graphitising inoculant, the mechanical properties similar to those obtained during the inoculation treatment carried out on cast iron with the recommended high sulphur content are achieved. The said operation increases the number of crystallisation nuclei for dendrites of the primary austenite. In this case, the iron particles act as substrates for the nucleation of primary austenite gp due to a similar crystallographic behaviour of the regular face centered cubic lattice The more numerous are the dendrites of primary austenite, the less free space is available in the interdendritic spaces for the formation of graphite eutectic grains, which makes the structure more refined (more eutectic grains) and the mechanical properties higher.